Mitigation of Harmonics and Unbalanced Voltage Disturbance Compensation by MSVPWM Based- DVR in the Distribution Net - Husen, Haider Muhamad (Kurdistan Journal of Applied Research, 2021)
Recent power distribution networks comprise abundant sensitive loads, which extremely impact the power quality of source in electrical power networks. Voltage dip, voltage rise, imbalanced voltage, line notching and distortion of harmonics are problems of power quality frequently take place. Pre-disturbance voltage compensation strategy and phase-locked-loop (PLL) based dq- space vector control are presented to improve a Dynamic Voltage Restorer (DVR), which restore the magnitude of voltage disturbance and displacement of phase angle to prior of voltage disturbance. 3-phase Multilevel strategy of Space Vector Pulse Width Modulation (MSVPWM) based- Multilevel Diode Clamped Converter (MDCC) is proposed as switching pulse signals employed low frequency, which creates high levels of voltage and fewer harmonics in the output waveform in comparison to 2-level SVPWM based- DVR. 3-level SVPWM based- DVR under balanced and imbalanced distortion voltage disturbances included sags and swells injected appreciated quantities of voltage, thereby attained ideal sinusoidal waveform with lower Total Harmonic Distortion THD% compared to 2-level SVPWM based- DVR. Furthermore, real and imaginary powers balanced effectively at sensitive load during various distortion voltage disturbance conditions via presented work. The proposed simulation model of multi-level SVPWM based- DVR is implemented by dedicating the software system of MATLAB/SIMULINK. The results of simulation exhibit the effectiveness and efficiency of the presented work under different distortion voltage disturbance conditions.